2003
DOI: 10.1021/ja030310s
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Light-Driven Structural Changes between the Mono- and Bilayer Stacking Alignments in 4-Octadecyloxystilbazolium Arylcarboxylate Films

Abstract: The present investigation deals with the light-driven morphological changes in multilamella films of N-methyl-4-octadecyloxystilbazolium arylcarboxylates (C18OStz+X-) cast on glass slides. The results of XRD analysis show a photostimulated layer expansion and shrinkage of the stacked thin films along the c-axis under alternative illumination at >350 and 254 nm, respectively. It was revealed that such lamellar changes could be switched either way by a reversible transformation between the mono- and bilayer unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The SQC16 was obtained as a yellow crystal: mp 176.5-177.0 °C. 1 H NMR (CDCl3), δ, ppm: 0.87 (t, 3H), 1.25-1.56 (m, 28H, (CH2)14); 4.0 (t, J ) 6.53 Hz, 2H, -OCH2); 6.9 (d, J ) 8. Chloroform was distilled before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SQC16 was obtained as a yellow crystal: mp 176.5-177.0 °C. 1 H NMR (CDCl3), δ, ppm: 0.87 (t, 3H), 1.25-1.56 (m, 28H, (CH2)14); 4.0 (t, J ) 6.53 Hz, 2H, -OCH2); 6.9 (d, J ) 8. Chloroform was distilled before use.…”
Section: Methodsmentioning
confidence: 99%
“…FT-IR spectra were recorded using a JASCO FT-IR 660 spectrometer. 1 H NMR spectra were recorded on a dm × 300 (Bruker) instrument. Elemental analysis was performed on a Carlo-Erba-1106 instrument.…”
Section: Methodsmentioning
confidence: 99%
“…58 Reversible light-driven morphological changes in multilamellar films of 24 cast on glass plates have been observed. 60 Controlled structural changes in the alignment begin with the photocyclodimerization of the stilbazolium moieties of aryl carboxylate salts. The syn-HH …”
Section: Dimeric and Polymeric Cyaninesmentioning
confidence: 99%
“…In general, however, it may be difficult to avoid phase separation as well as aggregation of the fluorophores in the matrixes during preparation, operation, or storage of the films, which cause a significant decrease of the PL efficiencies. Although applications of stilbene-type fluorophores, whose photolysis leads to nonemissive [2 + 2] dimers, to PL imaging have been also reported, these must be used in forms of well-aligned LB films …”
Section: Introductionmentioning
confidence: 99%
“…Although applications of stilbene-type fluorophores, whose photolysis leads to nonemissive [2 + 2] dimers, to PL imaging have been also reported, these must be used in forms of well-aligned LB films. 3 Recently, we demonstrated that nucleophilic substitution of poly(ethoxysilylenephenylene)s provides a convenient approach to variously substituted poly-(silylenephenylene)s. 4 In these reactions, highly electrophilic properties of the EtO-Si bond originate the smooth substitution on the polymers. 5 In the hope of obtaining single component and simply accessible PL imaging materials, we prepared poly(silylene-p-phenylene)s bearing an anthrylethynyl, pyrenylethynyl, or terthienyl group as the pendant by substitution reactions of poly[ethoxy(methyl)silylene-p-phenylene] with the corresponding organolithium reagents.…”
Section: Introductionmentioning
confidence: 99%